Hubungan Antara Kadar Trombosit Dan Kadar Hematokrit Terhadap Kejadian Demam Berdarah Pada Anak Di Puskesmas Mangkurawang Tenggarong - Zulaikha, Fatma; Permata, Nolva Indah; Muis, Abdul (Bunda Edu-Midwifery Journal (BEMJ), 2020)
Dengue Hemorrhagic Fever (DHF) or Dengue Fever is one of the health problems that occurs in children in the world, in Indonesia DHF cases can also lead to death in children. One of the efforts to reduce the mortality rate in children due to DHF is to identify risk factors that trigger DHF in children. This study aims to identify and analyze risk factors for the incidence of DHF in children. The design of this research is quantitative retrospective with cross sectional approach. The population in this study were pediatric patients at the Mangkurawang Tenggarong Public Health Center, Kutai Kartanegara in 2017-2019. The sampling technique in this study was purposive sampling and involved 101 pediatric patients. The analytical test used is the rank spearman. The results of the analysis test showed the platelet r value = -0.2123, the r value of the hematocrit = 0.298. This indicates that all these variables have a weak relationship to the incidence of DHF in children.